PENGARUH MEDIA SOSIAL TERHADAP OMZET PENJUALAN HANDPHONE DI OUTLET CENTRAL IT GRESIK (GEMA EKONOMI, 2018)
This study aims to determine the effect of social media on sales turnover in outlets Central IT Gresik. This study uses explanative quantitative research approach by using survey as a means of data retrieval that aims to find out how a variable affects other variables. The population in this study were all employees and visitors outlets with the number of 527 people. Sampling method using non-probability sampling method is saturated sampling because taking samples from all total population, using Likert scale, this research is survey research where primary data collected through questionnaires spread, secondary data collected from Central IT outlet and literature study. Data analysis method used is descriptive analysis method with simple linier regression analysis technique Crosstab as a tool to calculate whether there is relationship or influence between social media to sales turnover. Result of hypothesis in this research proved that social media have positive and significant effect to sales turnover where t count equal to 6,708 bigger than t table equal to 1,990. From Adjusted R Square = 0,352 it can be said that the change of dependent variable (Y) is 35,2% to variable X, while the rest 64,8% is caused by other factor not found in research.ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3477654